FORMULATION AND ANTIBACTERIAL ACTIVITY OF HERBAL TOOTHPASTE BASED ON ACEH TRADITIONAL MEDICINE - Rima Hayati; Amelia Sari; Rini Handayani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
This research is based on Acehnese traditional medicine containing betel leaf, areca nut, kencur rhizome, gambier sap, and clove buds. Traditionally, all parts of the plant are wrapped in betel leaf folds and chewed to maintain oral health. This study aimed to incorporate these ingredients into an herbal toothpaste and test its efficacy against bacteria that cause tooth decay, such as S. mutans and E. faecalis. Extracts from betel leaf, areca nut, aromatic ginger, gambier sap, and clove buds were used in this study. Based on variations in extract concentrations, three formulations were developed: F1, F2, and F3. In addition, F0 was the toothpaste base. The herbal toothpaste was light brown in color, homogeneous, semisolid, and had a characteristic betel leaf aroma, according to the evaluation results. The final product had a pH of 7.52–8.59, viscosity of 238.9–242.3 cP, and a foam height of 20 mm (F0), 11 mm (F1), 9 mm (F2), and 6 mm (F3). These values meet the toothpaste quality standard (SNI 112-3524-1995). While F1 showed moderate inhibition against S. mutans and E. faecalis in the antibacterial test, F2 and F3, showed high inhibition against S. mutans and moderate inhibition against E. faecalis. Based on these results, the optimal formula is F3 which has a larger inhibition diameter of 12.23 mm for S. mutans and 9.10 mm for E. faecalis. This herbal toothpaste can be developed to prevent oral candidiasis and gingivitis.  Keywords: herbal toothpaste, antibacterial activity, Streptococcus mutans, Enterococcus faecalis